2016
DOI: 10.1007/s10902-016-9732-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Size of Living Space and Subjective Well-Being

Abstract: Against a background of shrinking new homes and forebodings of ''rabbit hutch Britain'', the relationship between size of living space and subjective well-being has never been more topical in the UK. Using the British Household Panel Survey (BHPS) and fixed effects regressions, this paper is the first to examine this relationship comprehensively. Two pathways are proposed between space and subjective well-being. First, space facilitates values and activities. Second, space signals wealth which in turn influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 45 publications
3
60
0
2
Order By: Relevance
“…Another major finding about gender difference was that the mental health benefits of living in private housing or a relatively large flat were significant only for older men. A recent study also observed that the positive relationship between residence size and life satisfaction was only significant for men (Foye, ). Such gender difference is consistent with the perception that housing has more value for men than for women as a symbol of economic status (Foye, ), whereas for women, well‐being tends to be determined by their roles and relationships in domestic settings (Pinquart & Sörensen, ; Reid, ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another major finding about gender difference was that the mental health benefits of living in private housing or a relatively large flat were significant only for older men. A recent study also observed that the positive relationship between residence size and life satisfaction was only significant for men (Foye, ). Such gender difference is consistent with the perception that housing has more value for men than for women as a symbol of economic status (Foye, ), whereas for women, well‐being tends to be determined by their roles and relationships in domestic settings (Pinquart & Sörensen, ; Reid, ).…”
Section: Discussionmentioning
confidence: 85%
“…A recent study also observed that the positive relationship between residence size and life satisfaction was only significant for men (Foye, ). Such gender difference is consistent with the perception that housing has more value for men than for women as a symbol of economic status (Foye, ), whereas for women, well‐being tends to be determined by their roles and relationships in domestic settings (Pinquart & Sörensen, ; Reid, ). This could also explain why the protective role of healthy family functioning in mitigating mental distress is more significant for older women receiving CSSA.…”
Section: Discussionmentioning
confidence: 85%
“…However, contrary to much received wisdom, the most important positive factor seems to be a rich physical and social environment, and not simply the space available, at least within the constraints of a laboratory setup ( Bailoo et al, 2018 ). This is mirrored by a recent human study where, surprisingly, the size of houses per se has rather little effect on several indicators of overall subjective wellbeing ( Foye, 2017 ); this is a consideration that is becoming more important in the UK particularly, which now has the smallest new housing stock in Western Europe ( Morgan and Cruikshank, 2014 ). The question we need to ask is: how do we take into account this range of human environmental effects in clinical studies, just as we would with mice?…”
Section: Effects Of Environment On Ethologically Appropriate Behaviormentioning
confidence: 94%
“…Regarding indoor spaces, the size of the households is also an indicator of good quality of life. According to Foye (2017), in the UK, bigger houses can increase the level of subjective wellbeing, but only for a short period of time. Related to space efficiency, The Why Factory group at TU Delft carried out a design research project called On-The-Go (The Why Factory, 2018), in which the size of the living space is estimated by measuring the minimum space needed for daily activities like cooking or sleeping.…”
Section: Size Of the Living Spacementioning
confidence: 99%